5 - Sociopolitical Representations in African Cinema: Paulin S. Vieyra, Djibril Diop Mambéty, Eddie Ugbomah and Ola Balogun in the Footsteps of Ousmane Sembène - Diop, Samba (Africa Development, 2020)
This article discusses the innovative ways in which African filmmakers Ousmane Sembène, Paulin S. Vieyra, Djibril Diop Mambéty Eddie Ogbomah and Ola Balogun offer sociological insights into, and cultural representations of, African contemporary postcolonial societies. These filmmakers are able to highlight the breadth and depth of the undercurrents of hopes and impediments in Africa. Their themes include social justice, slavery, alienation, the advent of Islam and Christianity (upsetting the traditional beliefs and cosmogony in the process), military rule, tradition and modernity, Pan-Africanist ideals, the importation and imposition of the Western political system into Africa, and loaded concepts such as democracy, just to name a few. Ogbomah underscores the many travails that obtain in postcolonial Nigeria, the most salient being the ruthless corruption in the natural resources sector, primarily crude oil. These filmmakers try to offer a solid foundation on which modern Africa can, firstly, midwife the revival of a genuine indigenous model of economic development. Secondly, these filmmakers, each in his own peculiar style, provide artistic tools which can continue to support the development of a socially conscious and intellectually robust cinematic tradition in Africa.